Adherence to screening and management guidelines of maternal Group B Streptococcus colonization in pregnancy. (15th April 2022) - Pangerl, Sabine; Sundin, Deborah; Geraghty, Sadie
Abstract: Aims: To investigate Group B Streptococcus (GBS) colonization in pregnancy; adherence to antenatal GBS screening and adherence to the intrapartum antibiotics protocol within two models of care (midwifery and non‐midwifery led). Design: This retrospective quantitative study has employed a descriptive design using administrative health data. Methods: Data from five maternity hospitals in metropolitan and regional Western Australia that included 22, 417 pregnant women who gave birth between 2015 and 2019 were examined, applying descriptive statistics using secondary data analysis. Results: The study revealed an overall GBS colonization rate of 21.7% with similar rates in the different cohorts. A lower adherence to screening was found in the midwifery led model of care (MMC, 68.76%, n  = 7232) when compared with the non‐midwifery led model of care (NMMC, 90.49%, n  = 10, 767). Over the 5 years, screening rates trended down in the MMC with stable numbers in the counterpart. Adherence in relation to intrapartum antibiotic prophylaxis revealed discrepant findings between the study groups. Conclusion: Adherence to screening and management guidelines of maternal GBS colonization in pregnancy is lower within the MMC when compared with the NMMC. Impact: This is the first cohort study to describe the adherence to the recommended Western Australian GBS screening guidelines in the two different models of care. Findings may assist in the guidance and improvement of clinical protocols as well as the planning of clinical care in relation to GBS screening to reduce the risk of neonatal GBS infection.